Ion specificity at the peptide bond: molecular dynamics simulations of N-methylacetamide in aqueous salt solutions - Heyda, Jan; Vincent, Jordan C; Tobias, Douglas J; Dzubiella, Joachim; Jungwirth, Pavel (The journal of physical chemistry. B, 2010)
Affinities of alkali cations and halide anions for the peptide group were quantified using molecular dynamics simulations of aqueous solutions of N-methylacetamide using both nonpolarizable and polarizable force fields. Potassium and, more strongly, sodium exhibit an affinity for the carbonyl oxygen of the amide group, while none of the halide anions shows any appreciable attraction for the amide hydrogen. Heavier halides, however, interact with the hydrophobic methyl groups of N-methylacetamide. Using the present results for a model of the peptide bond we predict that the destabilizing effect of weakly hydrated Hofmeister ions, such as bromide or iodide, is not due to direct interactions with the backbone but rather due to attraction to hydrophobic regions of the protein.
Keywords: voda; roztoky; Peptides; peptidy; Molecular Dynamics Simulation; ionty; simulace molekulární dynamiky; acetamidy; Salts; Solutions; soli; Ions; Water; Acetamides